The spread of farming in the Eastern Adriatic - Forenbaher, Stašo (Documenta Praehistorica, 2006)
The beginning of farming in the Adriatic is a topic ripe for a new discussion and synthesis. Several lines of evidence suggest that immigration played a major role in the process. It invol- ved, however, both the actual movement of people and the active participation of the local population, and probably unfolded somewhat differently in different parts of the region. Thereis provocative evidence that the transition to farming occurred in a two-stage process. There was an initial stage of very rapid dispersal, perhaps by exploratory parties along the coast in the southern Adriatic. During the second stage, the eastern Adriatic littoral was probably colonizedby farming communities, while the hinterland remained an agricultural frontier zone.
Keywords: vzhodni Jadran; Croatia; Hrvaška; archaeology; arheologija; neolitik; kmetijstvo; agriculture; poljedeljstvo; poselitev; kolonizacija; migracije; human migration